2015
DOI: 10.1016/j.ijpara.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A linear mitochondrial genome of Cyclospora cayetanensis (Eimeriidae, Eucoccidiorida, Coccidiasina, Apicomplexa) suggests the ancestral start position within mitochondrial genomes of eimeriid coccidia

Abstract: The near complete mitochondrial (mt)genome for Cyclospora cayetanensis is 6184 bp in length with three protein-coding genes (Cox1, Cox3, CytB) and numerous lsrDNA and ssrDNA fragments. Gene arrangements were conserved with other coccidia in the Eimeriidae, but the C. cayetanensis mt genome is not circular-mapping. Terminal transferase tailing and nested PCR completed the 5’-terminus of the genome starting with a 21bp A/T-only region that forms a potential stem-loop. Regions homologous to the C. cayetanensis mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…has shown that partial mitochondrial cytochrome c oxidase subunit I (cox1) sequences are more reliable species-specific markers than complete nucleic SSU rRNA sequences, as they provide more synapomorphic characters [ 19 ]. The near complete genome of C. cayetanensis has been published recently [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…has shown that partial mitochondrial cytochrome c oxidase subunit I (cox1) sequences are more reliable species-specific markers than complete nucleic SSU rRNA sequences, as they provide more synapomorphic characters [ 19 ]. The near complete genome of C. cayetanensis has been published recently [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant clinical and public health importance of C. cayetanensis, genetic information was sparse (limited to ribosomal complex and heat-shock protein sequences) due to technical difficulties and limited accessibility of C. cayetanensis samples. Since 2014, FDA and CDC in collaboration with academia developed methods and strategies to sequence C. cayetanensis genomes, including complete mitochondrial and apicoplast genomes, and high quality whole genome assemblies using NGS technologies [11][12][13][14][15][16][17][18]. With the advances in NGS technologies, whole genome sequencing (WGS)-based typing has become a preferred approach in clinical and public health microbiology in the recent years [28].…”
Section: Discussionmentioning
confidence: 99%
“…Progress on the development of molecular epidemiologic tools to link cases with sources of infection has been hindered by the limited DNA sequence information. With the recent advances in sequencing technologies such as nextgeneration sequencing (NGS) and availability of efficient genome assembly programs, whole genome assemblies, complete mitochondrial and apicoplast genomes of C. cayetanensis have become available [11][12][13][14][15][16][17][18]. NGS is the preferred technology for generation of high-throughput high-resolution data in streamlined fashion for clinical diagnostics, forensic science, and public health research.…”
Section: Introductionmentioning
confidence: 99%
“…A TdT tailing method based on [ 48 , 49 ] was used as a method to verify that the linear conformation of the S. endobioticum mitochondrial genome. Positive and negative controls (i.e.…”
Section: Methodsmentioning
confidence: 99%